Assisted sexual coral recruits show high thermal tolerance to the 2023 Caribbean mass bleaching event - Miller, Margaret W.; Mendoza Quiroz, Sandra; Lachs, Liam; Banaszak, Anastazia T.; Chamberland, Valérie F.; Guest, James R.; Gutting, Alexandra N.; Latijnhouwers, Kelly R. W.; Sellares-Blasco, Rita I.; Virdis, Francesca; Villalpando, Maria F.; Petersen, Dirk (PloS one, 2024)
Assisted sexual coral propagation, resulting in greater genet diversity via genetic recombination, has been hypothesized to lead to more adaptable and, hence, resilient restored populations compared to more common clonal techniques. Coral restoration efforts have resulted in substantial populations of ‘Assisted sexual Recruits’ (i.e., juvenile corals derived from assisted sexual reproduction; AR) of multiple species outplanted to reefs or held in in situ nurseries across many locations in the Caribbean. These AR populations provided context to evaluate their relative resilience compared to co-occurring coral populations during the 2023 marine heat wave of unprecedented duration and intensity that affected the entire Caribbean. Populations of six species of AR, most ranging in age from 1–4 years, were surveyed across five regions during the mass bleaching season in 2023 (Aug-Dec), alongside co-occurring groups of corals to compare prevalence of bleaching and related mortality. Comparison groups included conspecific adult colonies as available, but also the extant co-occurring coral assemblages in which conspecifics were rare or lacking, as well as small, propagated coral fragments. Assisted sexual recruits had significantly lower prevalence of bleaching impacts (overall pooled ~ 10%) than conspecific coral populations typically comprised of larger colonies (~ 60–100% depending on species). In addition, small corals derived from fragmentation (rather than sexual propagation) in two regions showed bleaching susceptibility intermediate between AR and wild adults. Overall, AR exhibited high bleaching resistance under heat stress exposure up to and exceeding Degree Heating Weeks of 20°C-weeks. As coral reefs throughout the globe are subject to increasingly frequent and intense marine heatwaves, restoration activities that include sexual reproduction and seeding can make an important contribution to sustain coral populations.